Ivestigating of intimate lyrics in high school on the basis of noosphere education (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In the article modern methods and receptions of analysis of lyric work are grounded in connection with psychology and support on natural corresponding principle of forming of the integral  thinking (logical and figuratively-intuitional) with the use of all channels of perception that qualitatively influences on development of emotive and cognitive spheres of student and provides the recreation of educational material at creative level; there is  an authorial table of М. Rylskiy «Apple ripened» with application of the new going near the study of poetry on principles of  noosphere education the aim of that is  creation of educational view image as microstructures of knowledge from an object, laying of him in of long duration memory of student for the further use already by new  mental character.
Keywords: poem; art image; methods and techniques; noospheric education